The use of short stories in improving reading skills - Irhamni, M. Nabil; Nuzula, Nurfidausi; Indah Mala Rohmana, Wahyu (Lililacs Journal, 2025)
This study explores the effectiveness of short stories in improving reading skills among English as Foreign Language (EFL) learners, with a particular focus on the "previewing the text" method. The research examines how introducing students to key elements of a short story, such as characters, setting, and themes, before reading the full text enhances their reading comprehension, vocabulary acquisition, and engagement with the material. A qualitative approach was employed, involving a literature review and interviews with both students and teachers who have used short stories in their language learning and teaching practices. The findings reveal that short stories, when used in conjunction with the previewing technique, significantly boost students' ability to understand and analyse the text, foster critical thinking, and increase their vocabulary retention. The previewing method also helps students feel more prepared and less intimidated by unfamiliar words or complex structures, resulting in a more confident and motivated reading experience. The study highlights the potential of short stories to improve reading skills in EFL contexts and suggests that educators should integrate this approach into their curriculum to promote active engagement and deeper language development.